Patterns and reasons of migration to urban Odisha - Sumita Bera; Sibabrata Das (National Geographical Journal of India, 2022)
The study of changing patterns and reasons for migration has tremendous policy implications. Odisha as an economically developing state of India represents a very low level of urbanization but around fifty percent of the urban population are migrants. Analysing census of India data through commonly used measures of descriptive statistics, this paper studies the changing patterns and reasons for migration to urban places of Odisha. This paper is descriptive, yet has come up with new findings and raised a few questions requiring further investigation. The rising trend of urban-to-urban migration along with the feminisation of migration are two such issues.